POLICY REVIEW ON ISLAMIC EDUCATION IN THE OLD ORDER ERA IN INDONESIA - Irwansyah Suwahyu; Nurhilaliyah Nurhilaliyah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This article explains about some policies of Indonesian government in the old order era to the Islamic education. This study is a library research. The data obtained through the documents were analyzed by using content analysis. The research findings indicated that the Islamic education in the early of Indonesian’s independence day was not the concern of Indonesian government, whether it was a general policy as in the department of religious affairs or specifically as a policy in the study of religious education in schools. After PKI’s incident, the Islamic education received serious attention from the government such as policy requiring religious learning at every level of education. It was intended to eliminate the influence of the communist mind.Abstrak:Artikel ini menjelaskan tentang beberapa kebijakan pemerintah Indonesia di era orde lama terhadap pendidikan Islam. Penelitian ini adalah penelitian kepustakaan. Data yang diperoleh melalui dokumen dianalisis dengan menggunakan analisis isi. Temuan penelitian menunjukkan bahwa pendidikan Islam di awal hari kemerdekaan Indonesia bukanlah urusan pemerintah Indonesia, apakah itu kebijakan umum seperti di departemen urusan agama atau secara khusus sebagai kebijakan dalam studi pendidikan agama di sekolah. Setelah kejadian PKI, pendidikan Islam mendapat perhatian serius dari pemerintah seperti kebijakan yang mengharuskan pembelajaran agama di setiap tingkat pendidikan. Itu dimaksudkan untuk menghilangkan pengaruh pikiran komunis.